DIFFICULTIES ENCOUNTERED BY ENGLISH EDUCATION STUDENTS IN WRITING UNDERGRADUATE THESIS - Nadya Salsabila; Nike Angraini; Dita Rizki Anggraini (ELP (Journal of English Language Pedagogy), 2026)
Writing an undergraduate thesis is a crucial academic requirement; however, many English Education students face multiple challenges during the process. These difficulties often emerge from academic, linguistic, psychological, and social factors that interact in complex ways. While previous studies have examined these factors separately, few have analyzed them within a single comprehensive framework. This study aims to identify the major difficulties faced by English Education students in writing undergraduate theses and to analyze the contributing factors using Brown’s (2007) psychological, social, and linguistic dimensions. Employing a descriptive qualitative design, data were collected from 132 English Education students at four universities in South Sumatra through a closed-ended questionnaire and structured interviews. Quantitative data were analyzed descriptively, while qualitative data followed Miles and Huberman’s (2013) model. The findings revealed that academic factors were the most dominant (58.13%), followed by linguistic (22.12%), psychological (11.49%), and social (8.26%) factors. Students reported the greatest challenges in topic selection, paraphrasing, and maintaining motivation during supervision. The study underscores the need for stronger academic support, structured writing workshops, and consistent supervisory mentoring. These findings contribute to a more integrated understanding of thesis-writing difficulties and provide practical insights for improving academic writing instruction and supervision in EFL contexts.